Efeito da amoxicilina e do fluoreto no desenvolvimento do esmalte dentário de ratos - Souza, Juliana Feltrin [UNESP] (2013)
Background: Amoxicillin use in early childhood has been associated with molarincisor hypomineralization. Moreover, it has been supposed an association between amoxicillin and fluoride on enamel defects. Aim. This study aimed to evaluate in vivo the effect of amoxicillin and amoxicillin associated with fluoride on the enamel development of rat tooth. Materials and Methods: The research was divided into three studies. Chapter 1 – Fifteen pregnant Holtzman rats (Rattus norvegicus albinus) were divided randomly into three groups to receive saline (SG), 100 mg/kg/day amoxicillin (A100G), or 500 mg/kg/day amoxicillin (A500G), intragastrically, from days 13 to 22 of pregnancy. Twelve offsprings per group got the same dose until day 12. After 7 and 12 days, the specimens were fixed and embedded in paraffin. In the HEstained sections, the thickness of enamel matrix of upper molar germs was evaluated. Moreover, detection of amelogenin on day 7 and matrix metalloproteinase 20 (MMP - 20) on day 12 by immunohistochemistry were carried out. Chapter 2 - Fifteen rats (Rattus norvegicus, Albinus,Holtzman) were randomly divided into three groups to receive saline (SG), 100 mg/kg/day amoxicillin (A100G), or 500 mg/kg/day amoxicillin (A500G), as described in Chapter 1. Ten offspring per group received the same dose until day 40. The animals were euthanized on day 40. A total of 60 upper incisors and 60 upper first molars from 30 animals were dissected. Calcium (Ca) determination was performed by the compleximetric titration method and phosphorus (Pi) determination by colorimetric analysis using a spectrophotometer at 680 nm. A total of 30 lower first molars from 15 animals were analyzed under X-ray microtomography (XMT). Chapter 3 - Forty rats were, randomly, divided into four groups exposed to fluoride in water (100 ppm (mg F/L) or intragastric administration of amoxicillin (500 mg /kg body weight), according to the...